2016
DOI: 10.4236/ajps.2016.714187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photon Flux Density and Exogenous Sucrose on the Photosynthetic Performance during <i>In Vitro</i> Culture of <i>Castanea sativa</i>

Abstract: The low photon flux density (PFD) under in vitro conditions and sucrose added to the culture medium negatively limits the photochemical activity and photoprotective mechanisms of microshoots. In this work we hypothesize that decreasing sucrose in the culture medium in combination with increasing irradiance, could improve the photosynthesis and consequently the in vitro growth. We evaluated the effect of exogenous sucrose (30 and 5 g•L −1 , HS and LS, respectively), under different PFD (50 and 150 µmol photons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
(55 reference statements)
0
9
1
1
Order By: Relevance
“…Our study demonstrates the feasibility of propagating chestnut by TIS and CIS with the sugar supplementation reduced to one-sixth of the normal 3% used for this species. These results differ from those reported by Sáez et al [ 35 ], who concluded that to increase PPF from 50 to 150 µmol photons m −2 s −1 did not increase photosynthesis enough to sustain chestnut growth when sucrose was reduced from 3 to 0.5%. These authors cultured chestnut shoots in tubes with a semisolid medium and without forced ventilation, and in these conditions shoot growth is frequently sucrose-dependent, as shown for kiwifruit ( Actinidia deliciosa ) [ 36 ], Arabidopsis [ 37 ], Pfaffia glomerata [ 38 ] and Vernonia condensata [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our study demonstrates the feasibility of propagating chestnut by TIS and CIS with the sugar supplementation reduced to one-sixth of the normal 3% used for this species. These results differ from those reported by Sáez et al [ 35 ], who concluded that to increase PPF from 50 to 150 µmol photons m −2 s −1 did not increase photosynthesis enough to sustain chestnut growth when sucrose was reduced from 3 to 0.5%. These authors cultured chestnut shoots in tubes with a semisolid medium and without forced ventilation, and in these conditions shoot growth is frequently sucrose-dependent, as shown for kiwifruit ( Actinidia deliciosa ) [ 36 ], Arabidopsis [ 37 ], Pfaffia glomerata [ 38 ] and Vernonia condensata [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In Castanea sativa , Sáez et al [ 227 ] highlighted a correlation between light intensity and the addition of sugar to the growth medium. They demonstrated that HI (150 µmol m −2 s −1 ) and high sugar amounts (30 g L −1 ) produced an increase in photosynthetic activity and chlorophyll content and determined a higher proliferation rate and biomass production.…”
Section: Effects Of Light Intensitymentioning
confidence: 99%
“…Several authors report that high sucrose concentrations in the medium are deleterious for photosynthetic activity [5,26]. However, sucrose has also been reported to stimulate photosynthesis in in vitro plantlets [27,28]. ROS formation can also be stimulated [29] or decreased [30] by sugar.…”
Section: Discussionmentioning
confidence: 99%